Novel antiplatelet strategies targeting GPVI, CLEC-2 and tyrosine kinases. (2nd January 2021) - Harbi, Maan H.; Smith, Christopher W.; Nicolson, Phillip L. R.; Watson, Steve P.; Thomas, Mark R.
Abstract: Antiplatelet medications comprise the cornerstone of treatment for diseases that involve arterial thrombosis, including acute coronary syndromes (ACS), stroke and peripheral arterial disease. However, antiplatelet medications may cause bleeding and, furthermore, thrombotic events may still recur despite treatment. The interaction of collagen with GPVI receptors on the surface of platelets has been identified as one of the major players in the pathophysiology of arterial thrombosis that occurs following atherosclerotic plaque rupture. Promisingly, GPVI deficiency in humans appears to have a minimal impact on bleeding. These findings together suggest that targeting platelet GPVI may provide a novel treatment strategy that provides additional antithrombotic efficacy with minimal disruption of normal hemostasis compared to conventional antiplatelet medications. CLEC-2 is gaining interest as a therapeutic target for a variety of thrombo-inflammatory disorders including deep vein thrombosis (DVT) with treatment also predicted to cause minimal disruption to hemostasis. GPVI and CLEC-2 signal through Src, Syk and Tec family tyrosine kinases, providing additional strategies for inhibiting both receptors. In this review, we summarize the evidence regarding GPVI and CLEC-2 and strategies for inhibiting these receptors to inhibit platelet recruitment and activation in thrombotic diseases.